Avaliação morfométrica histológica e radiográfíca do remanescente dental da raiz mésio vestibular do primeiro molar superior após preparo cervical anticurvatura - Moura, Camilla Christian Gomes (2005)
The aim of this study was to perform histological and radiographic morphometric analysis of the dentin and dental remnants (dentin and cementum) of the distal wall of the upper molar buccal root (MV), after preparation by the Goerig technique. Twenty teeth were divided into two groups: control and experimental. The MV roots of the experimental group were instrumented by the Goerig technique and the control group did not undergo any treatment. All MV channels received contrast solution (100% barium sulfate) and were radiographed before and after instrumentation. The roots were decalcified in 5% nitric acid and sectioned below the furcation. The cervical segments of the roots were processed for paraffin inclusion, obtaining 5pm thick perpendicular cuts, which were analyzed by light microscopy. The HL Image program obtained measurements of the distal wall of the cervical third of the MV root in the histological sections and radiographs. Statistical analysis of the values ​​showed significant reduction in the dentin and dental remnants of the experimental group when compared to the control. The thickness of the radiographic dental remnant significantly reduced after preparation. In both groups the radiographic dental remnant was larger than the histological remnant, with significant difference. The results indicate that Goerig 's preparation technique significantly wears the distal wall in the cervical third in MV roots of the upper molars and that the values ​​of the radiographic dental remnant were thicker than the real one.